P.015 Demographics of Canadian neurosurgery residents – a national cross-sectional study from the Canadian Neurosurgery Research Collaborative. (17th June 2016) - Winkler-Schwartz, A; Bigder, M; Dakson, A; Elliott, C; Guha, D; Kameda-Smith, M; Lavergne, P; Makarenko, S; Taccone, M; Tso, M; Wang, B; Iorio-Morin, C
Abstract : Background: The Canadian Neurosurgery Research Collaborative (CNRC) is a new consortium of neurosurgery residency programs set-up to facilitate the planning and implementation of multi-center studies. As a trainee-led organization, it will focus on resident-initiated, resident-driven projects. The goal of this study is to assess the demographics of Canadian neurosurgery residents, with particular focus on their academic and subspecialty interests. Methods: After approval by the CNRC, an online survey will be sent to all Canadian neurosurgery residents and fellows with reminders at 2, 4 and 6 weeks. Anonymous, basic demographic data will be collected. Specific interest towards the various subspecialties, research and academic vs community practice will be measured. The data will be crossed with the ongoing Canadian Neurosurgery Operative Landscape study to assess the impact of case volume on academic and subspecialty interests. Results: This is the first study providing a snapshot of Canadian neurosurgery residents at all levels of training. The study is ongoing and the official results will be presented at the meeting. As one of the first CNRC studies, it will also demonstrate the effectiveness of the collaborative. Conclusions: Understanding the demographics and interests of Canadian neurosurgery residents will allow the CNRC to better fulfill its mission.